PENGARUH PROJEK PENGUATAN PROFIL PELAJAR PANCASILA TERHADAP KARAKTER DISIPLIN SISWA KELAS X PADA MATA PELAJARAN PPKN DI SMAN 14 SINJAI - Nurlaelah, Nurlaelah; Kasmawati, Andi; Hanafie, Nurharsya Khaer (Jurnal Tomalebbi, 2024)
The research approach used in this research is a quantitative approach. The population and sample in this research are all class X students at SMAN 14 Sinjai with a total of 74 students. The data collection techniques used in this research were interviews, questionnaires and documentation. The data analysis technique uses basic assumption tests, namely the normality test and linearity test, also using simple linear regression analysis tests, the t test and the coefficient of determination. The implementation of the project to strengthen the profile of Pancasila students is carried out systematically and fulfills the dimensions of the profile of Pancasila students, namely faith and devotion to God Almighty, noble character, global diversity, mutual cooperation, independence, critical reasoning and creativity. The research results stated that the implementation of the program was at a percentage of 36.5% which was included in the good category. Analysis of the average respondent questionnaire for variable P5 is in the agree category. The discipline character of class X students at SMAN 14 Sinjai is in the good category with a percentage of 41.9%. This can be proven through interviews with teachers. Apart from that, this was also confirmed by the results of the questionnaire of respondents who chose to agree. Several things that are indicators of assessment in this variable are student personality, behavior and attitudes. There is a significant influence of 24.6% regarding the influence of the project to strengthen the profile of Pancasila students on the discipline character of class X students in Civics subjects at SMAN 14 Sinjai. 75.4% was influenced by other factors not studied. It can be proven by the results of a linear regression test with the formula Y=14.229+0.570X. The Rsquare obtained was 0.246 at a significance level of 5%. Using the t test, a significance figure of 0.001 <0.05 was obtained. So on this basis, H0 is rejected. H1 is accepted, meaning that there is an influence of the project to strengthen the profile of Pancasila students on the discipline character of class X students in Civics subjects at SMAN 14 Sinjai.